2015
DOI: 10.1017/cjn.2015.278
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine for Status Epilepticus in Pediatrics

Abstract: Background: Our goal was to perform a systematic review of the literature on the use of intravenous lidocaine in pediatrics for status epilepticus (SE) and refractory status epilepticus (RSE) to determine its impact on seizure control. Methods: All articles from MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to November 2014), and gray literature were searched. The strength of evidence was adjudicated using both the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“… 56 Literature on the use of lidocaine in the treatment of SE is focused on its use for neonatal seizures and is beyond the scope of this review. 57 Yamamoto et al 58 in a survey of 194 neonatal ICUs at university hospitals in Japan found that lidocaine was useful in the treatment of neonatal SE.…”
Section: Resultsmentioning
confidence: 99%
“… 56 Literature on the use of lidocaine in the treatment of SE is focused on its use for neonatal seizures and is beyond the scope of this review. 57 Yamamoto et al 58 in a survey of 194 neonatal ICUs at university hospitals in Japan found that lidocaine was useful in the treatment of neonatal SE.…”
Section: Resultsmentioning
confidence: 99%
“…Electrographic or electro-clinical seizures frequently recur during weaning of pharmacologic coma medications [ 97 , 98 , 99 , 100 ], indicating that pharmacologic coma should be considered as a window during which specific therapies can be instituted for some status epilepticus etiologies and during which other anti-seizure medications can be initiated to provide additional coverage. Only case reports and series are available to guide management at this stage, and the options include topiramate [ 101 , 102 , 103 , 104 , 105 , 106 , 107 ], lacosamide [ 108 , 109 , 110 ], phenobarbital [ 111 , 112 , 113 , 114 ], ketamine [ 115 , 116 , 117 , 118 , 119 ], pyridoxine [ 120 , 121 , 122 , 123 , 124 , 125 ], neurosteroids [ 126 ], lidocaine [ 127 , 128 , 129 ], the ketogenic diet [ 90 , 102 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ], therapeutic hypothermia [ 137 , 138 , 139 , 140 , 141 ], immunomodulation [ 142 , 143 ], epilepsy surgery [ 115 , …”
Section: Management Of Refractory Status Epilepticusmentioning
confidence: 99%
“…Other marketed drugs such as lidocaine, felbamate, pregabalin, and gabapentin are used in SE, although the evidence is scarce [148][149][150]. Many unmarketed drugs for epilepsy treatment are being developed or studied with the goal of improving seizure control (adenosine-releasing silk, AMP-X-0079, 2-deoxy-glucose, huperzine A, imepitoin, minoclycine, NAX 801-2, pitolisant, PRX0023, VLB-01, glibenclamide, P2X7 receptor antagonist) [151][152][153][154][155][156][157][158][159][160].…”
Section: Othersmentioning
confidence: 99%